Optometric Evaluation and Management of Neuromyelitis Optica (NMO). - Schwartz, Sari R. (Optometry & Visual Performance, 2020)
Background: Neuromyelitis optica, a debilitating condition now regarded as a distinct disease entity, can be distinguished from other demyelinating conditions through optometric testing, including visual evoked potential, optical coherence tomography, and Goldmann visual field. Case Report: A 19-year-old African American female was referred by a local emergency department after presenting with asymmetric bilateral vision loss associated with numbness and tingling. After an episode of optic neuritis and myelitis, a brain MRI not meeting the diagnostic criteria for multiple sclerosis at disease onset, and detectable AQP4 antibodies, the patient was diagnosed with neuromyelitis optica. This report follows the patient's visual findings and miraculous recovery over seven visits. Several findings are tracked, including visual acuity, color vision, visual fields, macular and optic nerve thickness, and visual evoked potential. Conclusion: This case report demonstrates the corresponding and confirmatory roles of specialty optometric testing and may help identify future research treatment options.